Membuka Tabir Corrupt Campaign Practices Di Akhir Masa Jabatan Pejabat Politik di Indonesia - Najah, Nurun; Suryani, Ani; Arianty Nazib, Cindy Novia; Haya, Ulfa Syifaul; Puannandini, Dewi Asri (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2024)
Corruption is a major factor that undermines government credibility and diminishes the quality of public services. Corruption practices have evolved beyond legal issues to become part of the complex dynamics of political battles, particularly in the context of electoral processes. This study aims to analyze the forms of campaign corruption carried out by political officials at the end of their terms in office and to examine the implementation of law enforcement against political officials involved in campaign corruption in Indonesia. This research employs a normative juridical method, utilizing secondary data analysis, focusing on legal provisions related to criminal acts of corruption, especially campaign corruption, through a literature review and relevant theoretical analysis. The findings indicate that campaign corruption is a systemic issue that damages the electoral process and erodes public trust in government. Abuse of power manifests in various forms, including the use of state facilities, mobilization of government apparatus, and distribution of cash to gain support. The Indonesian government has attempted to address this issue through regulations such as Law No. 31 of 1999, Law No. 20 of 2001, and establishing the Corruption Eradication Commission (KPK). However, law enforcement efforts face several challenges, including political interference, poor coordination among law enforcement agencies, and weaknesses in the legal system that perpetrators of corruption exploit. The contribution of this research lies in identifying gaps in regulations and implementing law enforcement against campaign corruption. This study provides recommendations for strengthening inter-agency coordination, improving existing regulations, and enhancing transparency in electoral oversight, thereby supporting more effective efforts to combat corruption in Indonesia.